Novel design of a self powered and self sensing magneto-rheological damper - Ferdaus, Mohammad Meftahul; Rashid, Muhammad Mahbubur; Bhuiyan, Moinul; Asan Gani, Abdul Muthalif; Hasan, Muhammad Rabiul (IOP Publishing, 2013)
Magneto-rheological (MR) dampers are semi-active control devices and use MR fluids. Magneto-rheological dampers have successful applications in mechatronics engineering, civil engineering and numerous areas of engineering. At present, traditional MR damper systems, require a isolated power supply and dynamic sensor. This paper presents the achievability and accuracy of a self- powered and self-sensing magneto-rheological damper using harvested energy from the vibration and shock environment in which it is deployed and another important part of this paper is the increased yield stress of the Magneto rheological Fluids. Magneto rheological fluids using replacement of glass beads for Magnetic Particles to surge yield stress is implemented here. Clearly this shows better result on yield stress, viscosity, and settling rate. Also permanent magnet generator (PMG) is designed and attached to a MR damper. For evaluating the self-powered MR damper's vibration mitigating capacity, an Engine Mount System using the MR damper is simulated. The ideal stiffness of the PMG for the Engine Mount System (EMS) is calculated by numerical study. The vibration mitigating performance of the EMS employing the self-powered & self sensing MR damper is theoretically calculated and evaluated in the frequency domain.